Modelling of membrane fouling in ultrafiltration of Adsorbed Biotreated Palm Oil Mill Effluent (ABPOME) - Amosa, M. K.; Jami, Mohammed Saedi; Al-Khatib, Ma'an Fahmi Rashid; Jimat, Dzun Noraini; Muyibi, Suleyman Aremu (2014)
Organic matter and particles in wastewater are usually held responsible for most membrane pore blockings ultimately resulting in fouling during treatment processes. This study was conducted, for the first time, to elucidate the ultrafiltration (UF) membrane fouling phenomena caused by residual particulates in an adsorbed biotreated palm oil mill effluent (ABPOME) which is an end-of-pipe industrial wastewater from the palm oil processing industry. A laboratory-based bench scale experimentation using a cross flow membrane filtration system equipped with Polyethersulfone membranes of 1, 5, and 10 kDa UF, and operated at transmembrane pressures (TMP) of 40, 80 and 120 kPa was carried out. The experimental results revealed that the 5 kDa UF performed better with the particles contributing to a reversible type of fouling bringing about by cake layer formation mechanism with the highest coefficient of determination (R2) value of 0.9849. The flux-time curves have been analyzed using Hermia’s revised blocking filtration laws.